KOMPETENSI GURU AGAMA KRISTEN UNTUK PEMBELAJARAN DI ERA DIGITAL - Zebua, Frendi Sofyan (EKKLESIA: Jurnal Teologi dan Pendidikan Kristiani, 2023)
Abstract: Professional competence is an ability, teacher's skill in mastering learning which includes; designing, managing, implementing, and evaluating learning that is tailored based on competence, this research aims to describe in order to know and understand how important it is to develop the potential that exists within him. Teacher competence largely determines student success in the world of education, teacher professional activity is measured by the following points; the teacher masters the material he teaches, the teacher has mastered qualification standards and basic skills, the teacher is able to develop creative learning, the teacher knows how to do reflective activities and the teacher masters information technology to communicate. The title of this scientific work is Christian Religious Teacher Professional Competence for Learning in the Digital Age. The method used by researchers is the method of literature or literature, namely the data comes from books and journals. Based on the results of the research found by researchers, they found that learning was less effective because the teacher was less competent in teaching. A teacher is required to have competency in teaching and using technology. Abstrak: Kompetensi profesional adalah merupakan kemampuan, kecakapan guru dalam menguasai pembelajaran yang mencakup; merancang, mengelolah, melaksanakan, dan mengevaluasi pembelajaran yang disesuaikan berdasarkan kompetensi, maka peneliti ini bertujuan untuk mendeskripsikan agar mengetahui dan memahami betapa pentingnya untuk mengembangkan potensi yang ada dalam dirinya. Kompetensi guru sangat menentukan keberhasilan siswa dalam dunia pendidikan, aktifitas profesional guru diukur dengan poin-poin sebagai berikut; guru manguasai materi yang diajarkannya, guru telah menguasai standar kualifikasi dan keterampilan dasar, guru mampu mengembangkan pembelajaran secara kreatif, guru mengetahui melakukan kegiatan reflektif dan guru menguasai teknologi informasi untuk berkomunikasi. Judul karya ilmiah ini adalah Kompetensi Profesional Guru Agama Kristen Untuk Pembelajaran Di Era Digital. Metode yang digunakan peneliti adalah metode kepustakaan atau literatur yaitu datanya bersumber dari buku-buku dan jurnal. Berdasarkan hasil penelitian yang ditemukan oleh peneliti, menemukan bahwa pembelajaran kurang efektif diakibatkan karena guru kurang cakap dalam mengajar. Seorang guru diharuskan untuk memiliki kompetensi dalam mengajar dan menggunakan teknologi.